Introduction to the SDGS in the 2030 agenda: the general principle of sustainability - Santiago A. Bello Paredes (Opción, 2021)
This study makes an introduction to the SDGs contained in the 2030 Agenda, making an in-depth assessment of the scope and legal effects of sustainability as a general guiding principle of this international action.